DECOUPLING OF P- AND CORG-BURIAL FOLLOWING EARLY CRETACEOUS (VALANGINIAN-HAUTERIVIAN) PLATFORM DROWNING ALONG THE NW TETHYAN MARGIN - Van De Schootbrugge B.; Adatte T.; Steinmann P.; Föllmi K.; Kuhn O. (My University, 2003)
During the Hauterivian three important phases of platform drowning, phosphogenesis and mesotrophic carbonate deposition along the northern margin of the Tethys are not mirrored by positive δ[13]Ccarb excursions such as during the Valanginian and Aptian, but rather by decreasing to stable trends. The aim of this study is to understand the decoupling of organic carbon and phosphorus burial during the Hauterivian. For this purpose PO4-concentrations were determined from biogenic limestones from eight sections along a platform to basin transect. Integration with a previously obtained dataset for the Valanginian leads to a biostratigraphically calibrated high resolution phosphorus accumulation rate (mg/cm2/kyr) curve based on 575 data points. From the Late Valanginian to Early Hauterivian phosphorus accumulation rates increased nearly threefold from 0.75 mg/cm2/kyr to 2.1 mg/cm2/kyr. The phosphorus accumulation rate increase obtained in this study correlates well with a compilation based on ODP and DSDP records, indicating that phosphorus accumulation rates along the northern margin of the Tethys reflect global changes in P in- and output. A global rise in continental P input is thought to have resulted from intensified greenhouse climate conditions leading to increased riverine runoff. Coeval sea-level rise led to re-arrangement of circulation and oxygenation of bottom waters, which meant that P was increasingly well retained by means of Fe- and Mn-oxyhydroxides. Furthermore, the NW margin of the Tethys may have been especially susceptible to phosphogenesis as it was influenced by cold water exchange with the Boreal Realm and prone to coastal upwelling. The Late Hauterivian witnessed sea-level fall, more sluggish circulation along the NW Tethyan margin and also globally lower weathering and erosion rates, leading to generally lower phosphorus accumulation rates. Increased regeneration of phosphorus might have occurred as circulation stagnated and bottom water oxygen levels decreased. Increased phosphorus input into Early Hauterivian oceans did not lead to the production of organic carbon-rich rocks, but rather to increased carbonate carbon burial, also seen in a decoupling between the δ[13]Ccarb record (decreasing) and phosphorus accumulation rates (increasing). Decoupling of these records reflects the ecological recovery of the carbonate system after a prolonged phase of reef destruction during the late Early and Late Valanginian. Carbonate production in the green water mode dominated by filter feeding calcitic organisms may have been forced, despite high nutrient levels, in order to bring down increased alkalinity.
Keywords: Hauterivian; phosphorus; carbon isotopes; palaeoceanography; platform drowning; Valanginian; Mesozoic::Cretaceous::Lower::Hauterivian; Mesozoic::Cretaceous::Lower::Valanginian; Мезозой::Меловая::Нижний::Валанжинский; Мезозой::Меловая::Нижний::Готеривский